Standardization of planting time for optimum growth and oil production of gera- nium (Pelargonium graveolens L. Her.) under north Indian plains - Mohd Yaseen, Man Singh, Saudan Singh, (Journal of Spices and Aromatic Crops, 2008)
The effect of different planting dates on survival, growth, yield and oil characteristics ofgeranium (Pelargonium graveolens L. Her.) was studied at Lucknow (Uttar Pradesh). Freshterminal stem cuttings were planted on different dates starting from 31 October 2002 to March2003 at 15 days interval. Cuttings planted in mid December recorded significantly highersurvival (93.5%), fresh biomass (539.7 q ha-1) and essential oil yield (54.9 kg ha-1) than earlieror later planted cuttings.